Asymptotically Periodic Solutions of Neutral Partial Differential Equations with Infinite Delay - Henriquez-Miranda, H (2013)
In this paper we discuss the existence and uniqueness of asymptotically almost automorphic and S-asymptotically w-periodic mild solutions to some abstract nonlinear integro-differential equation of neutral type with infinite delay. We apply our results to neutral partial differential equations with infinite delay.
Keywords: Neutral functional differential equations; integro-differential equations; asymptotically almost automorphic functions; S-asymptotically omega-periodic functions